EXPERIENCE IN ORGANIZING OF THE WORK OF THE MOBILE TEAM OF CARDIOVASCULAR SURGEONS IN KUZBASS - Султанов, Роман Владимирович; Казакова, Ольга Станиславовна; Лихачева, Татьяна Юрьевна; Московская, Елена Викторовна; Архангельский, Валерий Вениаминович (Medicine in Kuzbass, 2019)
The experience of organizing the work of the visiting team of cardiovascular surgeons in Kuzbass to identify hemodynamically significant stenoses of the carotid arteries is presented. The experience gained has shown that the formation and work of an on-site team with the participation of an ultrasound diagnosis doctor and an angiosurgeon can detect hemodynamically significant asymptomatic stenosis of the carotid arteries, and timely surgical treatment of this group of patients can significantly reduce cardiovascular mortality in the Kuzbass.
Keywords: Kuzbass; carotid artery stenosis; carotid endarterectomy